Bone Marrow Aspiration Cytology in Diagnosing Hematological Disorder in a Tertiary Care Center - Kafle, Neeta; Upadhaya Kafle, Santosh; Singh, Mrinalini; Sinha, Amrita; Sedhain, Sapana; Bhattarai, Soorya (Birat Journal of Health Sciences, 2024)
Introduction: Bone marrow aspiration is a safe, simple and minimally invasive procedure used for evaluation of hematological disorder. It is useful when diagnosis from the first line investigations are inconclusive. Objectives: To compare the clinical findings and bone marrow aspiration cytology findings Methodology: This is a prospective hospital based cross sectional study carried out in Birat Medical College. Simple random consecutive sampling was done in patients that underwent bone marrow aspiration from December15th 2021 to June 14th 2022. Dry tap, patient under treatment and inadequate material were excluded from the study. After informed consent, BMA was done from the right or left posterior superior iliac crest using local anesthesia. Smeared slides were stained by Wright stain and was examined by two pathologists. Special stain was not done. Ethical clearance was taken from Institutional Review Committee (IRC). Data collected was then tabulated by using Microsoft Excel sheet and SPSS Results: A total of 106 patients were included in this study with majority aged > 45 years (50.9%). The commonest indications for bone marrow aspiration was anemia under evaluation (35.9%) followed by pancytopenia under evaluation (22%). The most common diagnosis identified by bone marrow aspiration was mixed nutritional deficiency anemia (21.7%).In patients evaluated for pancytopenia six were diagnosed with hematological malignancy. Conclusion: Nutritional deficiency anemia, commonly indicated for bone marrow aspiration, was the most common cause diagnosed by bone marrow aspiration. Bone marrow aspiration is important to arrive at diagnosis especially in patients with anemia and pancytopenia.